KONSTRUKSI SOSIAL MEKANISASI ATAS BURUH PEREMPUAN TANI DI PEDESAAN (UIN Sayyid Ali Rahmatullah Tulungagung, Indonesia, 2017)
In rural areas, traditionally female farmers have an important role in production, particularly during the harvest season and growing season. Women farmers, feed their families by getting jobs during the harvest. During the harvest period it has received significant income for women farmers in their households. In the agricultural tradition, the role of women farmers is very important, not only their length of work, but also their intensity. But since the Green Revolution and the mechanization, newly introduced rice and systematic types of technology have ignored and displaced the roles and jobs of women farmers. The inclusion of the technology created is easy to be controlled by male farmers, then the process of eviction of women peasants was inevitable avoid. Keywords: Social Construction, Mechanization, Women Farm Laborers